Prophetic Leadership of Madrasah Principals in Instilling Akhlakul Karimah at MTsN Tulungagung: A Multi-Case Study at MTsN 1 and MTsN 5 Tulungagung - Khoirudin Suja’i; Abd. Aziz; Ahmad Tanzeh (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Prophetic leadership of madrasah principals represents a highly significant leadership phenomenon. Various cases of bullying, brawls, sexual violence, and promiscuity have become serious threats for students, raising deep concern among parents. The existence of madrasah tsanawiyah is considered highly relevant for instilling akhlaqul karimah in the present era. Many parents place great expectations on madrasah tsanawiyah to provide their children with beneficial knowledge and to nurture noble character, whether in their conduct toward fellow human beings, toward the natural environment, or toward Allah SWT. The aim of this research is to explore the prophetic leadership of madrasah principals in cultivating akhlaqul karimah. The study employs a qualitative descriptive approach with a multi-site design. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis was conducted using single-case analysis and cross-case analysis. The validity of the data was ensured through credibility, transferability, dependability, and confirmability. The findings reveal that: (1) The vision of prophetic leadership among madrasah principals in instilling akhlaqul karimah is to develop students with the characteristics of the Profil Pelajar Pancasila and as rahmatan lil-‘alamin, grounded in exemplary conduct and implemented through several programs, including habituation activities, value-based learning, Qur’anic memorization and literacy, Friday infaq, role modeling, and collaboration with parents/guardians. (2) The integrity of prophetic leadership is reflected in serving as a role model, adopting an empathetic approach, being honest and transparent in delivering information and policies, assuming responsibility for all assigned duties, and consistently monitoring the moral conduct of students.